A soft continuum robot, with a large variable-stiffness range, based on jamming. (13th September 2019) - Zhao, Yanzhi; Shan, Yu; Zhang, Jie; Guo, Kaida; Qi, Lizhe; Han, Longguang; Yu, Hongnian
Abstract: Inspired by the physiological structure of the hand capable of realizing the continuous change in finger stiffness when grasping objects of different masses, a self-locking soft continuum robot with a large variable-stiffness range based on particle jamming and fibre jamming is proposed in this paper to meet the requirements of it in practical application. In this paper, a variable stiffness range is derived due to the good fluidity and rigidity of the spherical particles and the low elasticity and high toughness of the fibres. Then, an analysis model is established to deduce its self-locking condition, and the deflection angle of self-locking under the influence of external force is about 0.17 rad. The maximum stiffness of the experimental prototype can reach 1223.58 N m −1 due to the limitation of the experimental materials, despite the fact that the theoretical stiffness can be increased infinitely after self-locking. To explain the adaptability of the robot, the adaptive conditions of the soft continuum robot with variable stiffness are deduced. A new evaluation index, the adaptive intensity of the soft continuum robot, is introduced and the adaptability experiments are carried out. In adaptability experiments, the maximum bending angle of the continuum robot reaches 108°. Finally, the adaptability of the soft continuum robot to different geometries is discussed.